2011
DOI: 10.4172/2155-9597.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Concentration in Malarial Patients by Flame Photometer

Abstract: Malaria is a life-threatening disease caused by the parasite. It could be a major public health problem in Pakistan due to poor hygienic conditions; malnutrition borne non-defensive immunity system. The purpose of study was to examine possible changes in electrolytes level of patients with malaria. Serum electrolytes were determined by using appropriate techniques. The result showed a significant elevation in the levels of sodium (Na) and potassium (K), whereas, chloride decreases statistically in malarial pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…Result of the present study agrees with the report of Baloch et al. (2011) that found decreased chloride level but increased sodium and potassium levels in malaria-infected human individuals when compared with control. Similarly, Ikekpeazu et al.…”
Section: Discussionsupporting
confidence: 93%
“…Result of the present study agrees with the report of Baloch et al. (2011) that found decreased chloride level but increased sodium and potassium levels in malaria-infected human individuals when compared with control. Similarly, Ikekpeazu et al.…”
Section: Discussionsupporting
confidence: 93%
“…This study demonstrated a significant decline in plasma zinc levels in patients with vivax malaria compared to normal individuals, which agrees with one of the earlier studies (9). Zinc concentration was four-fold higher in plasmodium infected red cells than the uninfected ones indicating the need for acquisition of zinc atoms into RBCs by the parasite before hemolysis can occur (10).…”
Section: *Significant Discussionsupporting
confidence: 91%
“…In the assessment phase for eligibility, out of the 68 studies scrutinized, 60 were subsequently excluded for several reasons, mainly in vitro studies. Eight studies from the main databases were considered eligible 20 23 , 33 36 . Additional resources were utilized, including Google Scholar and a review of reference lists from studies in the main databases.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, reviewing the reference lists from the main databases yielded two more studies that fit the inclusion criteria 40 , 41 . In total, 13 studies were deemed suitable for inclusion in the review 20 23 , 33 41 (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%